CARDIOSPASM AND CARDIA ACHALASIA A III-IV UNSATISFACTORY RESULTS OF CARDIO DILATORY ANALYSIS OF CAUSES: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Ligay, R.E.; Babajanov, K.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The impossibility of cardiodilatation is the unsatisfactory reason for less invasive methods of treatment of patients with achalasia of the cardia, the impossibility of carrying out a cardiopulmonary dilator, and the directly unsatisfactory reason for dilatation courses aimed at expanding the cardia. In case of ineffectiveness and impossibility of dilatation, surgical treatment is recommended.